PCB Layout Detection Using Eucledian Distance Algorithm - Muhammad Ikhwanus; T.Iqbal Faridiansyah; Zulfikar (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
In the image identification process, the determination of geometric coordinate transformations must be in line with thetwo images. To identify the tested image, the size of similarity is defined by the alignment quality of these two images,which measures the similarity between the tested and the fixed image. So that to detect PCB layout, it also be determinedby matching the PCB image reference feature with the tested PCB image based on differences in the imaging conditionsresult. Ideally, a good similarity measurement has almost a zero deferent value and a larger value for different images.Therefore, the Eucledian distance algorithm is proposed in this paper to detect similarity among PCBs layout with 15training image and 30 tested images samples. Each training image has a varying reduction quality of image. From thesimulation results can be concluded that this algorithm can be used in a detecting similarity of PCB layout